Nuclear Magnetic Resonance and Quantum Chemical Calculations of Ca+2 Doped Norepinephrine Molecule by Using DFT and HF Methods - Yılmaz, Mücahıt; Kebiroğlu, Mehmet Hanifi (My University, 2024)
Norepinephrine plays an important role in many processes such as stress response, attention, alertness, blood pressure regulation, neurotransmission and emotional states. In this study, the molecule was optimized in order to get knowledge about the formation of the Ca+2 doped norepinephrine complex and the functions of norepinephrine in neurotransmission or other cellular processes by interacting with calcium. Quantum mechanical calculations such as FT-IR, Nuclear Magnetic Resonance (NMR), HO-MO-LUMO structure with the energy level diagram, UV-visible absorption, The density of states (DOS) of the optimized molecule were performed. The physical and chemical structure characteristics of the norepinephrine molecule and the change of its structural properties by molecular bonding with Ca+2 were investigated.
Keywords: HF; NMR; DFT; FT-IR; UV- Vis